Effect Of Heat Treatment On Cellulose Crystallinity Of Empty Fruit Bunch Oil Palm Fiber And Its Relation To The Dimensional Stability Of Medium Density Fiberboard - Abdul Hafid, Siti Munawarah (2005)

(untitled)
Oil Palm (Elaeis guinensis) is an important commercial agriculture plant in Malaysia generating a vast amount of residues, in the form of oil palm trunk (OPT), oil palm frond (OPF) and empty fruit bunch (EFB) which have high potential as raw material in wood-based industry. However, these lignocellulosic materials have poor dimensional stability i.e., high thickness swelling and water absorption. Cellulose crystallinity has been reported to influence the physical properties of the fibers. This study attempts to increase the cellulose crystallinity of oil palm EFB fiber via heat treatment and aimed i) to evaluate the effect of heating temperature on the cellulose crystallinity of oil pal EFB fiber ii) to determine the effect of cellulose crystallinity on thickness swelling (TS) and water absorption (WA) of Medium Density Fiberboard (MDF) made from heat treated oil palm fibers and iii) to establish relationship between cellulose crystallinity and TS and WA.Oil palm EFB fibers were heated for two hours at different temperatures, 150°C 160°C, 170°C, and 180°C. Untreated samples were used as control. The crystallinity and crystallite size of the cellulose molecules were investigated using X-ray diffraction (XRD) technique. Chemical analyses were also conducted on both heat treated and untreated EFB fibers to determine the proximate amount of lignin, cellulose and hemicellulose. MDF with the size of 130mm x 130mm x 5mm were produced from these fibers. The density of the MDF was 700 Kgm-3. The effects of cellulose crystallinity to the TS and WA of board were examined. The proximate amount of chemical components in the EFB fiber in this study was found comparable with those of conventional wood. The lignin content was in the range of 20-27%, cellulose content was 40-47% and hemicellulose content was 23-25%. The results shows that crystallinity of oil palm EFB cellulose were 21.05% for untreated fiber, 27.09% for fiber heated at 150°C, 26.68% at 160°C, 26.53% at 170oC and 30.84% at 180oC. The corresponding crystallite sizes of the cellulose sample were 3.22 nm, 3.42 nm, 3.64, 3.38 nm and 2.93 nm respectively. Heat treatment was found to increase the cellulose crystallinity of EFB fiber but did not markedly affected the crystallite size. In this study, MDF made from heat treated EFB of oil palm fiber was found to have relatively high TS and WA and failed to pass the Japanese Industrial Standard (JIS A 5906 – 1983). The TS were 15.9% in the MDF from untreated fiber,16.5% for the MDF from fiber heated at 150°C,16.3% at 160°C, 15.3% at 170°C and 15.6% at 180°C. Meanwhile the WA of the MDF boards was 77.7%, 81.0%, 79.5%, 83.2% and 71.8%, respectively. It was found that the increase in temperature in this study gave no effect to the TS but reduce the WA only at temperature of 180°C. This study found that there were no trend found in the relatioship between cellulose crystallinity with TS and WA at various temperatures as the R-squares were very small. There was also no direct effect of increase in cellulose crystallinity to the TS and WA of MDF as the R-squares were very small. Even though the cellulose crystallinity of EFB fiber increased by heat treatment, it was not sufficient to impart dimensional stability to the MDF board.